The Impact of The Cedaw Convention : Paths to Equality - Byrnes, Andrew (Washington, DC: World Bank, 2012)
The Convention on the Elimination of All Forms of Discrimination against Women (the "CEDAW Convention", or "the Convention") was adopted by the United Nations over thirty years ago. Described by some as an "international bill of rights for women", the Convention has been an important tool used by national and international advocates for the equality of women, while the Committee established under the Convention to monitor its implemenation has played a significant role in encouraging the implementation of the treaty.